2002
DOI: 10.1128/ec.1.4.634-642.2002
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Independent Roles for a Gα i Protein and Adenylyl Cyclase in Regulating Development and Stress Responses in Neurospora crassa

Abstract: Growth and development are regulated using cyclic AMP (cAMP)-dependent and -independent pathways in Neurospora crassa. The cr-1 adenylyl cyclase mutant lacks detectable cAMP and exhibits numerous defects, including colonial growth habit, short aerial hyphae, premature conidiation on plates, inappropriate conidiation in submerged culture, and increased thermotolerance. Evidence suggests that the heterotrimeric G␣ protein GNA-1 is a direct positive regulator of adenylyl cyclase. ⌬gna-1 strains are female-sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 69 publications
6
58
0
3
Order By: Relevance
“…Components of the macroconidiation pathway have been identified in both Neurospora and the filamentous fungus A. nidulans, and known upstream signalling proteins seem to be conserved in both species 58 . In contrast, there is little conservation of downstream components between the two fungi.…”
Section: Growth and Development Hyphal Growthmentioning
confidence: 99%
“…Components of the macroconidiation pathway have been identified in both Neurospora and the filamentous fungus A. nidulans, and known upstream signalling proteins seem to be conserved in both species 58 . In contrast, there is little conservation of downstream components between the two fungi.…”
Section: Growth and Development Hyphal Growthmentioning
confidence: 99%
“…GanB has conserved domains that are considered mutants from VER7 and six from RMS011 were isolated to be directly involved in interaction with the guanine and the deletion of ganB was checked by genomic Southnucleotide found in all G␣-proteins (Simon et al 1991; ern analysis. The fact that the transcripts of the ganB Skiba et al 1996;Bohm et al 1997), as well as the myrisgene were not detected by Northern analysis of these toylation site in the N terminus (Buss et al 1987). The mutants and sequencing the flanking region of inserted amino acid sequence of GanB shows 75-90% identity argB showed that the deletion was successful (data not to the amino acids of GpaB (Liebmann et al 2003) and shown).…”
Section: Tive and Constitutively Inactive Mutants Of The Ganb Gene: mentioning
confidence: 99%
“…The cAMP/PKA system is also involved downstream of group III G␣-protein signaling GTP bound and the free ␤␥-complex may interact with many types of downstream effectors such as enzymes in some processes such as cell proliferation, development, stress response, mating, and virulence (Kü bler (adenylate cyclases, phosphodiesterases, phospholipases, etc.) and ion channels, which in turn initiate signals via et al 1997;Kruger et al 1998;Alspaugh et al 2002;Ivey et al 2002;Liebmann et al 2003). second messengers such as cyclic AMP, diacylglycerol, inositol triphosphate, and/or critical ions in the signal A dominant activating mutation in the fadA gene, encoding a G␣-subunit of the filamentous fungus Aspertransduction pathway (Neer 1995;Bohm et al 1997;Neves et al 2002).…”
Section: G Uanine Nucleotide-binding Proteins (G Proteins)mentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the effect of downstream flanking region was ligated into the BamHI site cAMP on production of aerial hyphae, 2 mm cAMP (Sigma, St. of pBP27. The 2-kb XhoI-XhoI upstream flanking region of Louis) was added to standing VM liquid cultures as described mak-2 was PCR amplified from plasmid pBP30 with T7 and previously Ivey et al 2002). To test for MAK1 (containing an XhoI site) primers and ligated into the conidiation in submerged liquid cultures, conidia were inocuXhoI site to produce pBP-KOMAK2.…”
mentioning
confidence: 99%